The Effect of Hold Time Variation in the Annealing Process To Mechanical Properties and Microstructure of Austenitic Manganese Steel - Ilham Azmy; Albert Daniel Saragih (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2020)
Manganese steel is a special alloy steel which has good mechanical properties, especially high ductility and toughness values. This steel has high work hardening capability so it will be easy to engineer. In industrial applications, this steel is susceptible to a decrease in the value of its mechanical properties such as the hardness value due to continuous loading. From these problems, a steel engineering process is needed in order to significantly improve the mechanical properties of steel so that it has good durability and lifetime. This study aims to determine the effect of holding time of heat annealing treatment process on the microstructure and mechanical properties of austenitic manganese steel. This research was conducted by heating the annealing process at a temperature of 1000 oC with four variations of holding time for 0, 40, 80, and 120 minutes. After the austenitic manganese steel specimen is heated for a certain time, it is then subjected to very high temperature cooling (in the furnace). The steel specimen is then prepared for metallographic testing and mechanical properties (hardness) testing. Metallographic testing is carried out to be able to analyze the microstructure formed in the austenitic manganese steel specimens after undergoing annealing process. From the metallography results, it was found that the effect of holding time on the annealing process affected carbide precipitation at the grain boundaries in the austenite matrix of manganese steel specimens. In the annealing process with a holding time of 80 minutes, the austenitic manganese steel showed a microstructure with perfect carbide precipitation at the grain boundaries so that this would have an effect on a significant increase in the hardness value. From the results of the hardness test, it was also found that the hardness value of steel specimens by annealing process for 80 minutes was 39.5 HRc. Thus, the effect of the optimal holding time of the annealing heat treatment process to improve the microstructure and mechanical properties (hardness value) is 80 minutes.